Ethnomedicinal validation of Telfairia occidentalis L. leaf: a dual experimental and computational approach to uterine leiomyoma therapy - Ogunlakin, Akingbolabo Daniel; Gyebi, Gideon Ampoma; Elbasyouni, Amel; Awosola, Oyindamola Esther; Dada, Moyosoluwa Mary; Akinmurele, Opeyemi Josphine; Adegoke, Abdullahi Adeyemi; Oladoja, Israel Kunle; Adelakun, Ajibola David; Oluwadara, Omolola; Banwo, Gabriel Olalekan; Adediran, Adedayo Johnson; et al. (Frontiers in Nutrition, 2025)
IntroductionA nutrient-dense vegetable with Ethnomedicinal use for treating oxidative and fibrotic diseases is Telfairia occidentalis L., often known as “ugu” in Nigeria. Although it has been used extensively in the past, neither experimental nor computational methods have been used to characterize its antifibrotic potential. This study investigates the antioxidant, enzyme-inhibitory, and antifibrotic effects of aqueous T. occidentalis leaf extract in albino rats with MSG-induced uterine leiomyomas, employing in silico modeling to understand the underlying molecular mechanisms.MethodsIron chelation, NO scavenging, and DPPH radical scavenging properties of T. occidentalis aqueous extract were evaluated, using quercetin serving as the standard. The inhibitory effects of the extract on α-amylase, α-glucosidase, monoamine oxidase (MAO), and acetylcholinesterase (AChE) were evaluated. Testosterone, FSH, LH, and oestradiol levels were measured in MSG-induced fibroid rats treated with T. occidentalis aqueous extract. The tissues of the uterus and ovaries of treated rats were examined histologically. Furthermore, the HPLC-identified compounds in the extract were docked against STEAP4.Results and discussionThe extract demonstrated modest antioxidant activity; however, it was less effective than quercetin at scavenging NO radicals, DPPH, and iron-chelating capacity. It demonstrated AChE and MAO inhibition that was dose-dependent, with an IC50 for MAO inhibition of 0.178 ± 0.003 μg/mL that was comparable to donepezil (0.155 ± 0.005 μg/mL). α-Amylase activity increased in a dose-dependent manner, whereas α-glucosidase inhibition remained lower than the control. Testosterone and oestradiol levels in T. occidentalis-treated fibrotic rats significantly decreased, suggesting that MSG-induced hormonal abnormalities were corrected. Despite some epithelial deterioration, histopathological results showed partial recovery of uterine integrity and restoration of ovarian architecture with growing follicles. These results may suggest that the leaf extract of T. occidentalis exhibits antifibrotic and Hormone-modulating properties. HPLC identified beta-carotene and lutein affinity for STEAP4 was discovered by computational methods, suggesting a synergistic process. Through a combination of hormone-regulating, enzyme-inhibitory, and antioxidant properties, T. occidentalis shows encouraging antifibrotic efficacy. These results support its traditional application and demonstrate its applicability in the development of phytotherapeutics for the treatment of uterine leiomyomas.